The Acoustics of the Catacombs - IANNACE, Gino; TREMATERRA, Amelia; QANDIL, Ahmad (Archives of Acoustics, 2014)
The catacombs are underground places. This paper reports the results of acoustic measurements carried out inside the catacombs of “San Gennaro” (Naples) and in those one of “San Callisto” (Rome). Originally the catacombs were also used to perform sacred functions, although we don’t know the type of these functions i.e. if they were spoken, sung or performed as psalms. This paper presents acoustic measurements carried out in catacombs using the impulse response method, and by the analysis of the monaural acoustic parameters, (T_30, EDT, C_80, D_50 and STI), the authors intend to understand the type of religious ceremony performed in the catacombs. If the catacombs had been reverberant places, they could not have been used for prayers because the echoes would have created difficulties in concentration and meditation for the devotees due to the poor speech comprehension.